Individualized parotidectomy to reduce the incidence of postoperative facial paralysis for primary benign parotid neoplasms - Yu Zhou; Xianjie Duan; Chengyun Si; Chuanjun Chen; Hui Peng; Zhihong Zhang (Elsevier, 2022)
Objective: The aim of this study was to evaluate the role of individualized parotidectomy to reduce the incidence of postoperative facial paralysis for primary benign parotid tumors. Methods: A total of 154 consecutive patients who underwent individualized parotidectomy for benign parotid gland neoplasms were retrospectively reviewed. We analyzed the incidence and the significant risk factors associated with postoperative facial paralysis after individualized parotidectomy. Results: Postoperative transient FP was observed in 25 patients (16.2%). None of the patients developed a recurrence or permanent facial paralysis. Grade II facial nerve function was predominant (92.0%) and no patient had grade VI. Among the 25 patients, the facial nerve function of 93.6% of patients recovered in 3 months, and function had recovered in 100% of patients in 6 months. Tumor location, tumor size and surgery extent were the significant and independent risk factors associated with postoperative facial paralysis after individualized parotidectomy. Conclusion: Individualized parotidectomy can effectively reduce the incidence of postoperative facial paralysis and shorten the recovery time of facial nerve injury for primary benign parotid neoplasms.